Detection of Microscopic Characters And Evaluation Of The Anti-Inflammatory Effect Of Anagallis Arvensis L. Wildly Grown In Karbalaa’ Countryside - Kabbani, Fareed Mohamed Fawaz; Harami, Thanaa Mohamed; Mahdi, Fatimah Mohammed Saeed; Bader, Qasim Allawi (South Eastern European Journal of Public Health, 2024)
Anagallis arvensis is a well-known herb wildly grown in Karbalaa’ countryside. The aim of the study was to detect some microscopic features for the dried-grinded roots, leaves, flowers and seeds of the plant and evaluate the effect of the alcoholic extract of the aerials part (AEAP) on acute inflammation induced by egg-white model. Microscopic identification was done using an optical microscope. For the evaluation of the anti-inflammatory effect, rats were divided into 4 groups (n=6), the negative control group, the positive control (Diclofenac sodium) group, AEAP 4 mg/kg was applied to group 3 individuals and AEAP 7 mg/kg was applied to group 4. The extracts and the positive control were I.P. injected. The results of the microscopic test revealed several diagnostic characters, such as cluster oxalate crystals and xylem vessels with pitted walls in the roots. Glandular trichomes composed of one- or two-celled stalk and a spherical, unicellular head and Fragments of the fibrous layer of the anthers in the flowers, Anomocytic stomata in the leaves. The (AEAP) of A.arvensis showed an anti-inflammatory effect in both 4mg/kg and 7 mg/kg doses compared to the negative control [p<0.01], while no statistically significant differences were noticed between the results of extract’s groups and the results of the positive control group.